Gelatin coating increases in vivo bone formation capacity of three-dimensional 45S5 bioactive glass-based crystalline scaffolds - Westhauser, Fabian; Senger, Anne-Sophie; Obert, David Peter; Ciraldo, Francesca E.; Schuhladen, Katharina; Schmidmaier, Gerhard; Moghaddam-Alvandi, Arash; Boccaccini, Aldo R. (Journal of tissue engineering and regenerative medicine, 2019)
Recent studies have demonstrated that surface characteristics, porosity, and mechanical strength of three-dimensional 45S5-type bioactive glass (BG)-based scaffolds are directly correlated with osteogenic properties. Three-dimensional BG-based scaffolds obtained from maritime natural sponges (MNSs) as sacrificial templates exhibit the required morphological properties; however, no in vivo data about the osteogenic features are available. In this study, uncoated (Group A) and gelatin-coated (Group B) crystalline MNS-obtained BG-based scaffolds were evaluated mechanically and seeded with human mesenchymal stem cells prior to subcutaneous implantation in immunodeficient mice. Before implantation and after explantation, micro-computed tomography scans were conducted, and scaffolds were finally subjected to histomorphometry. Scaffolds of both groups showed bone formation. However, Group B scaffolds performed distinctly better as indicated by a significant increase in scaffold volume (8.95%, p = 0.039) over the implantation period compared with a nonsignificant increase of 5.26% in Group A scaffolds in micro-computed tomography analysis. Furthermore, percentage bone area was 10.33% (±1.18%) in the Group B scaffolds, which was significantly (p = 0.007) higher compared with the 8.53% (±0.77%) in the Group A scaffolds in histomorphometry. Compressive strength was enhanced significantly by gelatin coating (9 ± 2 vs. 4 ± 1 MPa; p = 0.029). The presence of gelatin on the remnant parts was verified by scanning electron microscopy and X-ray spectroscopy, demonstrating the coatings' resilience. MNS-obtained BG-based scaffolds were thus confirmed to exhibit osteogenic properties in vivo that can significantly be enhanced by gelatin coating.